EFEKTIVITAS EKSTRAK ETANOL DAUN BIDARA (Ziziphus mauritina) TERHADAP DAYA VERMISIDAL Fasciola sp - Muhammad Agus Munandar Putra; Mashur; Katty Hendriana Priscilia Riwu; Septyana Eka Rahmawati (SANGKAREANG, 2024)
Fasciolosis is a parasitic disease that often attacks ruminant livestock and causes losses for farmers in the form of reduced livestock productivity and can even cause death. This disease is caused by infection with the worm Fasciola sp. This study aims to determine the effectiveness of ethanol extract of bidara leaves (Ziziphus mauritina) on the vermicidal power of Fasciola sp. The samples used in this study were adult fasciola worms taken from the Majeluk Slaughterhouse (RPH) and bidara leaf extract. This research used a Completely Randomized Design (CRD) with seven treatments and three replications each. The treatment consists of bidara leaf extract with a concentration of 2.5%; 3.5%; 4.5%; Albendazole with a concentration of 2.5%; 3.5%; 4.5% as a positive control and use of distilled water as a negative control. The data obtained were analyzed using variance and continued with the Duncan test. The results of this study showed that the use of bidara leaf extract had a significant effect (P<0.05) on vermicidal fasciola sp. The higher the concentration of bidara extract and Albendazole, the faster the death of Fasciola sp. The use of bidara leaf extract and Albendazole 4.5% is the most effective concentration when compared with concentrations of 2.5% and 3.5%. However, of the bidara leaf extract and Albendazole, the most effective is Albendazole 4.5% with the fastest worm death time, namely 4.37 minutes.